The Economic Value of Book Loans – The Case of the Municipal Library of Prague - Stejskal, Jan; Hájek, Petr; Řehák, Tomáš (My University, 2016)
In recent years, the value of public library services has tended to be evaluated using the contingent valuation method. This is able to reveal readers' hidden preferences. However, it appears that the total value of a public library as expressed by one number leads to a methodological bias related to the difficulty of assessing the value of one standard book loan. Moreover, this approach does not reflect the needs of the public libraries’ management. Therefore, this study focuses on a detailed investigation of the most important public library service, book loans. For this purpose, we have employed statistical models to identify the significant determinants of willingness to pay (WTP) for book loans and WTP for purchasing books, respectively. The results suggest that loan services have the greatest perceived value for students, people who are economically active. Management who are interested in increasing the success of their institution across society must also know the perceived value of individual books so that they can adjust their library's acquisition policy. It was found that novels had the highest perceived value, followed by educational literature in the fields of economics and education as well as information science. This entirely new analytical method of measuring WTP for public services raises many new implications that could change the strategies of individual libraries – as well as the public policy strategies of donors and library ownership.
Ekonomická hodnota výpůjčky knihy - případová studie Městské knihovny v Praze
Keywords: public libraries; economic value; book loans; case study; veřejné knihovny; ekonomická hodnota; výpůjčky; případová sudie